New psychosocial interventions for bipolar disorder: A review of literature and introduction of the systematic treatment enhancement program - Miklowitz, D; Otto, M (2006)
What is the evidence that psychosocial treatment adds to the efficacy of pharmacotherapy in forestalling episodes of bipolar disorder (BPD)? This article gives the rationale for including psychosocial intervention in the outpatient maintenance of BPD. Attention is placed on 4 psychosocial modalities that have achieved empirical support in randomized trials: family-focused psychoeducational treatment (FFT), cognitive-behavioral therapy (CBT), interpersonal and social rhythm therapy (IPSRT), and group psychoeducation. FFT, CBT, and IPSRT are being contrasted with a psychosocial control condition in the context of the ongoing, multicenter Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD). The objectives, design, and potential contributions of the STEP-BD study are explained. Future directions for the evaluation and dissemination of manual-based psychosocial interventions are discussed. © 2006 Springer Publishing Company.